2017
DOI: 10.1002/2016jb013499
|View full text |Cite
|
Sign up to set email alerts
|

Locally and remotely triggered aseismic slip on the central San Jacinto Fault near Anza, CA, from joint inversion of seismicity and strainmeter data

Abstract: We study deep aseismic slip along the central section of the San Jacinto Fault, near the Anza Seismic Gap, in southern California. Elevated strain rates following the remote Mw7.2, 4 April 2010 El Mayor‐Cucapah and the local Mw5.4, 7 July 2010 Collins Valley earthquakes were recorded by Plate Boundary Observatory borehole strainmeters near Anza and were accompanied by vigorous aftershock sequences. We introduce a method to infer the distribution of triggered aseismic slip from combined seismicity and geodetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 84 publications
14
52
0
Order By: Relevance
“…Most applications have considered simple stressing, such as a step change in shear stress due to a large earthquake. Some studies have looked at more complicated stressing histories and shown the model to be consistent with observations or independent data sets such as geodetic data (e.g., Dieterich et al, ; Green et al, ; Inbal et al, ; Segall et al, ; Ziv, ). However, as was previously mentioned, there is still need for further verification.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most applications have considered simple stressing, such as a step change in shear stress due to a large earthquake. Some studies have looked at more complicated stressing histories and shown the model to be consistent with observations or independent data sets such as geodetic data (e.g., Dieterich et al, ; Green et al, ; Inbal et al, ; Segall et al, ; Ziv, ). However, as was previously mentioned, there is still need for further verification.…”
Section: Introductionmentioning
confidence: 88%
“…This was also investigated by Helmstetter and Shaw () who found an analytical expression that maps seismicity rate and cumulative number of events to stress change. A number of observational studies have utilized this result (e.g., Inbal et al, ; Savage, ) since seismicity rate and cumulative number of events can be estimated directly from data. Spatially heterogeneous stresses were explored by Helmstetter and Shaw (), who related the p value of Omori's law to stress heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…However, here source interactions have been taken into account. In application of the Dieterich theory for joint inversion the role of earthquake interactions and secondary events is often cited (e.g., Inbal et al, ; Segall et al, ) as an element of uncertainty in determining the applied stress field. Equation provides a possible resolution as it allows us to separate the externally applied stress field Spfalse(tfalse) and the changes that occur through source interactions.…”
Section: Theorymentioning
confidence: 99%
“…However, in many applications of the Dieterich theory the cumulative number of events (or seismicity rate) is not simulated. Instead, observed seismicity rate and cumulative number of events are used to extract the changes in stress (e.g., Dieterich et al, 2000;Helmstetter & Shaw, 2009;Inbal et al, 2017;Ziv, 2012).…”
Section: Interactions That Are Discrete In Timementioning
confidence: 99%
“…In addition, rainfall and barometric pressure are measured at all the strainmeters, and pore pressure at some of the strainmeters in Cascadia and California. Since installation in 2005, strain signals related to many geophysical phenomena are observed in the strainmeters, including tide (Hodgkinson et al, ; Lu & Wen, ; Roeloffs, ), earthquake (Barbour et al, ; Inbal et al, ; Roeloffs, ), aseismic creep (Inbal et al, ; Langbein, ; Roeloffs, ), episodic tremor and slip (Dragert & Wang, ; Hawthorne & Rubin, ; K. Wang et al, ), groundwater extraction (Barbour & Wyatt, ), and lake seiche (Luttrell et al, ).…”
Section: Observation Of Long‐period Deformationmentioning
confidence: 99%